TINDAK LANJUT PENGEMBANGAN DIKLAT TEKNIK PELEDAKAN PADA PENAMBANGAN BAHAN GALIAN - Wanda Adinugraha; Zanescaya Wirasangka (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2017)
The passing rate of the blaster training in mining tended to decline from 2005 to 2014 with an averagedecline of 20%, while the participants of training rose sharply and peak in 2013 as many as 234 participants.To find out the condition that lead to the decrease of passing rate, the Center of Training and Education ofMineral and Coal conducted a study by distributing questionnaires to alumni of 2nd- class blaster. As a result298 questionnaires responded by the alumni. From the study, it is identified that participants of blaster trainingmeet a difficulty to learn and understanding the handbook that applies, while the duration of the training itselfis considered too short. For that reason there is an idea to split the blasters training into two types of trainingbased on explosives knowledge and blasting technique. It is inportant to develop the model of blaster trainingthat is able to meet the criteria of blast competency under the considerations of the hierarchy and support ofmine blaster assignment.